The role of political leadership in the development of regional organization : the case of Pakistan in SAARC - Mia, Mohammad (My University, 2020)
SAARC'ın gelişimi dalgalı bir süreçtir. Bazen kuruluş, bazı çığır açan başarılara tanık olurken, bazen gelişme süreci çıkmaza girmiştir ve bazen kuruluş, yıllık toplantılar gibi ilkesel konularda dahi hareketsiz kalmıstır. Pakistan ve Hindistan’ın ikili ilişkiler durumu SAARC’ın gelişimi için bir motordur. Pakistan’ın siyasi liderlerinin çatışma politikasını dengeleyerek Hindistan'a karşı durması veya bandwagoning stratejisini takip ederek Hindistan ile işbirliği yapmaları SAARC'ın gidişatını önemli ölçüde etkilemektedir. Bu nedenle tez, Pakistan siyasi liderliğini bir vaka çalışması olarak ele alınmıştır. Hindistan'daki siyasi liderlik durumunun, ayrı bir çalışmanın konusunu teşkil edebileceği düşünülmektedir.Bu çalışma, SAARC'ın gelişiminde Pakistan siyasi liderliğinin rolünü belirlemeyi ve değerlendirmeyi amaçlamaktadır. Bu tezde, siyasi liderlik terimi Oran Young’un yapısal liderlik düzeyinde ele alınmaktadır. Andrew Moravcsik'in üçlü işlevleri çerçevesi –politika başlatma, arabuluculuk ve seferberlik– SAARC'ın geliştirilmesinde Pakistan'ın siyasi liderlik rolünü belirlemek için kullanılmıştır.Tezde, SAARC'ın gelişiminde Pakistan'ın siyasi liderliğinin rolünün, yalnızca SAARC içi gelişmelere odaklanmak yerine Hindistan ve Pakistan'ın ikili ilişkilerine odaklanarak daha iyi belirlenebileceğini ileri sürülmüştür. Ayrıca tez, üye devletlerin SAARC gelişiminin ve ikili ilişkilerinin birbirleriyle korelasyona sahip olduğunu ve üye ülkelerin ikili bağları olmadan SAARC’ın gelişimini değerlendirmenin düşünülemez olduğunu iddia etmektedir. Hindistan ve Pakistan, hem bölgede hem de SAARC'da her açıdan en önemli ve önde gelen aktörlerdir. SAARC’ın gelişiminin Hindistan ve Pakistan arasındaki ikili ilişkilerle doğrudan bir bağlantısı vardır. Başka bir deyişle, Hindistan-Pakistan ilişkilerindeki uzlaşma veya yakınlaşma SAARC’ın gelişimini olumlu etkilerken, gerilimin tırmanması SAARC'ın gelişimini tam tersi yönde etkilemiştir.

The development of SAARC is a fluctuating process. While sometimes the organization witnesses some breakthrough achievements, its development process has been timely deadlocked, and sometimes the organization could not act in principle matters such as the annual gathering. Pakistan and India’s bilateral relations situation is an engine for SAARC development. Pakistani political leadership stance toward India if they pursue the policy of conflict to India by balancing her or cooperate with India by following the strategy of bandwagoning, significantly impact the course of SAARC. Thus, for this very reason, the thesis takes the Pakistani political leadership as a case study. The Indian political leadership case can be a separate specific study.This study aims to determine and evaluate the role of Pakistani political leadership in the development of SAARC. The thesis approached the term political leadership on a structural political leadership level in the class of Oran Young that stands for national leaders. The triad functions framework of Andrew Moravscik –policy initiation, mediation and mobilization –was used to determine the Pakistan political leadership role in the development of SAARC. The thesis asserts that the role of Pakistani political leadership in the development of SAARC can be determined better by focusing on the bilateral relations of India and Pakistan, rather than focusing solely on Intra-SAARC developments. Also, the thesis claims that SAARC development and bilateral relations of the member states have a correlation with each other, and it’s unthinkable to evaluate SAARC development without bilateral ties of the member countries. India and Pakistan are the major and leading players in all aspects both in the region and in the SAARC. SAARC development has a direct linkage with the bilateral relations between India and Pakistan. In other words, while détente or rapprochement in the India-Pakistan relations positively impacts the SAARC development, tension escalation influences SAARC the vice versa.
Keywords: Bölgeslleşme; Development; Gelişim; Hindistan Regionalism; India; International relations; Pakistan; Political Leadership; Political science; SAARC; Siyasal bilim; Siyasi Liderlik; Uluslararası ilişkiler